2021
DOI: 10.1021/acsptsci.0c00181
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of Novel UGT1A1 Variants Including UGT1A1 454C>A through the Genotyping of Healthy Participants of the HPTN 077 Study

Abstract: Cabotegravir (CAB) is an integrase strand-transfer inhibitor of HIV that has proven effective for HIV treatment and prevention in a long-acting injectable formulation, typically preceded by an oral formulation lead-in phase. Previous in vitro studies have demonstrated that CAB is primarily metabolized via glucuronidation by uridine diphosphate glucuronosyltransferase (UGT) 1A1 and 1A9. In this study, we performed next-generation sequencing of genomic DNA isolated from the HPTN 077 partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…HPTN 077 also found that CAB-LA had a longer terminal phase half-life among participants with an above median BMI, as compared to participants with a below median BMI [ 32 ]. An additional study from HPTN 077 found that genetic variants of enzymes that metabolize CAB-LA exist and could affect the rate at which CAB-LA is metabolized [ 47 ]. A better understanding of variability of CAB-LA's pharmacokinetics could improve optimization of dosing tailored to different populations.…”
Section: Discussionmentioning
confidence: 99%
“…HPTN 077 also found that CAB-LA had a longer terminal phase half-life among participants with an above median BMI, as compared to participants with a below median BMI [ 32 ]. An additional study from HPTN 077 found that genetic variants of enzymes that metabolize CAB-LA exist and could affect the rate at which CAB-LA is metabolized [ 47 ]. A better understanding of variability of CAB-LA's pharmacokinetics could improve optimization of dosing tailored to different populations.…”
Section: Discussionmentioning
confidence: 99%
“…The longer terminal half‐life was also associated with unsplit injection, higher body mass index, and shorter needles [36]. Polymorphism in enzymes metabolising CAB‐LA may also affect the pharmacokinetics of the drug [37]. Additional research will be needed to better understand the variability of the tail phase between different populations.…”
Section: Issues About Cab‐la In Hiv Preventionmentioning
confidence: 99%